Analisis Pengaruh Rasio Keuangan Terhadap Prediksi Kondisi Financial Distress - Emia Eunike Violine Ginting; Endah Dwi Kusumastuti (Indonesian Accounting Research Journal, 2023)
This research aims to analyze the effect of financial ratio in predicting financial distress. The data used in this research is the secondary data with the population of the hotel, restaurant, dan tourism companies listed on the Indonesian Stock Exchange. The sample is determined by the method of purpovive sampling so that the number of sample in this research as much as 24 companies. The result of this research is there is a significant positive influence of Current Ratio in predicting financial distress conditions; there is a significant positive influence of Return On Assets in predicting financial distress conditions; there is a significant negative effect of Debt to Assets Ratio in predicting financial distress conditions; there is a influence is not significant of Total Assets Turnover in predicting financial distress conditions; there is a influence is not significant of Sales Growth in predicting financial distress conditions; there is a simultaneous influence of Current Ratio, Return On Assets, Debt to Assets Ratio, Total Assets Turnover, and Sales Growth in predicting financial distress conditions.